Crisis, cracks, and the emancipatory struggle for food and food sovereignty - Guerra, Lúcia Dias da Silva; Alfonso González, Georgina (Argumentum, 2026)
Humanity is experiencing a global capitalist crisis, which has been ongoing since 2008. This has been accompanied by a poly-crisis in which several crises have converged and interconnected: food (hunger, food production, obesity, and malnutrition), health, economic (inflation and recession), ecological (climate and pandemic) and geopolitical (war and international divisions). It is around food that gender relations, and individual and collective identities, are constructed and challenged. This article addresses the emancipatory struggle for food and food sovereignty, and the political uses of hunger, from theory to practice, in Latin America and the Caribbean, and its new contours within the contemporary context. This is a critical study that uses historical-materialist theory as a research method and dialectical argument as a method of exposition. It seeks to understand the crisis as the cracks where we have the greatest possibility of echoing our struggles against capital.
Keywords: Marxism; Capitalism; Crisis; Food; Food Sovereignty